The implementation of the synectic’s model to improve creative thinking - Yasrina, Raisa; Suryawati, Suryawati; Zubaidah, Tuti (Geuthèë Institute, Aceh, 2025)
Creative thinking skills are important skills that students must possess in order to face the challenges of 21st century learning. However, initial observations show that students' creative thinking skills, especially in mathematics learning, are still relatively low. This study aims to enhance students' creative thinking skills through the implementation of the Synectic’s learning model in Grade VII of SMP Negeri 13 Banda Aceh. The study employs a quantitative approach with a one-group pretest-posttest experimental design. The study population consists of all Grade VII students at SMP Negeri 13 Banda Aceh, with a sample of one class, Grade VII-2, randomly selected from five parallel classes. Data were collected through a creative thinking ability test and analyzed using the Wilcoxon test. The test results showed that the W value was 276 and the critical value was 73, so 276 > 73. This indicates a significant improvement in students' creative thinking abilities after the implementation of the Synectic’s learning model. These findings suggest that the Synectic’s model is effective in stimulating students to think fluently, flexibly, and originally through the use of analogies in the learning process. The implications of this study are that the Synectic’s learning model can be used as an alternative learning strategy capable of fostering the development of students' creative thinking skills at the junior high school level.